Analysis of Students’ Work Readiness Based on Self-Efficacy of Vocational High School in The Building Information Modelling Technology Era - Permana, Asep Yudi; Fitriani, Fitriani; Aulia, Taufik (Journal of Technical Education and Training, 2023)
This research was conducted based on social phenomena related to the high level of student anxiety in facing the development of the digital era when carrying out industrial practices due to low confidence in students’ abilities. BIM is software for simulating all information in a three-dimensional model that is not only an image, but also a development project system, management, method, and work steps. Therefore, this study aims to determine the relationship between students’ self-efficacy and work readiness of Vocational High Schools in facing the Building Information Modelling (BIM) technology era that developed during construction work. BIM as a form of a management information system requires middle-class employees to work jointly as a team. In the field of AEC, the process of planning and design, development, as well as maintenance is performed collaboratively. Furthermore, a total of 360 students in West Java were selected as participants using proportional stratified random sampling. Data were collected using product-moment analysis. The results showed that self-efficacy was positively and significantly related to work readiness with a correlation coefficient of r= 0.692 and p-0.000 where p<0.05. This means that the increase in self-efficacy helps to develop work readiness and vice versa. The coefficient of determination shows that self-efficacy and other variables contribute 47.9% and 52.1%, respectively, to students’ work readiness in facing the BIM technology era. This can be interpreted that the higher the self-efficacy, the lower the presentation anxiety and vice versa. Based on the results of this study as recommendations for improvement, it is necessary to carry out additional learning activities to increase student skills, so that student confidence will increase when working.